Notes on the genus Rhyncocheilus in China (Coleoptera, Staphylinidae, Staphylininae) with descriptions of three new species - Tang, Liang; Schillhammer, Harald; Zhao, Xin (Zootaxa, 2021)
Three new species of Rhyncocheilus from China are described: R. huanghaoi sp. n. (Xizang), R. gonggashanus sp. n. (Sichuan) and R. yangxiaodongi sp. n. (Yunnan). The characters of R. griseosericans (Fairmaire, 1894) are clarified. Rhyncocheilus rugulipennis Cameron, 1932 is new to China, and R. henanensis Schillhammer, 2012 is new to Hubei. A key to the Chinese species of the genus is provided.